Ambient air quality monitoring of particulate matter in around waste facilities - Amir, Aziz; Rizalman, Mamat; Abdul Adam, Abdullah; Roziah, Zailan (2016)
The experiment is undertaken to determine the particulate matter concentration in a landfill Jerangau-Jabor., Kuantan Pahang. Air pollution associated with the atmospheric particulate matter has diverse effect ranging from human health to visibility and climate forcing. Operating municipal solid waste (MSW) landfills emit a variety of air pollutants, among them particulate matter (PM) and landfill gas. Much attention has been given to landfill gas emission due to their climatic impact and their potential for energy production. However, particulate matter (PM) has also important effects on local air pollution and human health. The concentration of particulate matter has been taken for 8hours and comparison at 3 different location of landfill also has been performed. The PM measurement in the landfill was performed using a Direct sense monitoring kit model TG 501 which is a portable and battery operate. Base on the experiment testing that has been done; it is shown that the data display data logging was successfully recorded. After the particulate matter measured had been done, data from the probe is gained through iPAQ hx2700 Series Pocket PC, data mass of particulate matter is gained through PC software. The average concentration of particulate matter at the landfill site range 519.41μg/m3 –942.54 μg/m3. The higher concentration was observed at the point C (the disposal of domestic waste) because the type of municipal solid waste from a residential area, market and business area within 300-500 tonnes/day.